2016
DOI: 10.1007/s00122-016-2785-0
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of Fusarium head blight resistance in three related durum wheat populations

Abstract: Key message The QTL Fhb1 was successfully introgressed and validated in three durum wheat populations. The novel germplasm and the QTL detected will support improvement of Fusarium resistance in durum wheat. AbstractDurum wheat (Triticum durum Desf.) is particularly susceptible to Fusarium head blight (FHB) and breeding for resistance is hampered by limited genetic variation within this species. To date, resistant sources are mainly available in a few wild relative tetraploid wheat accessions. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 78 publications
5
78
0
Order By: Relevance
“…A recent study (Prat et al 2016) reported the successful introgression of Fhb1 from hexaploid wheat into T. durum resulting in improved resistance. The effect of Fhb1 from Sumai-3 has been assessed in three durum wheat crosses between an Fhb1 harbouring experimental T. durum line and three European T. durum cultivars.…”
Section: Improvement Of Fhb Resistance In Durum Wheatmentioning
confidence: 99%
“…A recent study (Prat et al 2016) reported the successful introgression of Fhb1 from hexaploid wheat into T. durum resulting in improved resistance. The effect of Fhb1 from Sumai-3 has been assessed in three durum wheat crosses between an Fhb1 harbouring experimental T. durum line and three European T. durum cultivars.…”
Section: Improvement Of Fhb Resistance In Durum Wheatmentioning
confidence: 99%
“…The wheat/Fusarium pathosystem is race non‐specific as shown previously (e.g., Mesterházy, Bartok, Mirocha, & Komoroczy, ; Van Eeuwijk et al., ); that is, the genotypes show no significant ranking differences according to the isolate (Voss, Bowden, Leslie, & Miedaner, ). FHB resistance in durum wheat is similarly inherited than in bread wheat showing a continuous variation (Prat et al., ; Somers, Fedak, Clarke, & Cao, ) with a high impact of genotype × environment interaction (Miedaner & Longin, ). The range from high to low susceptibility, however, is smaller than in bread wheat (Prat et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…FHB resistance in durum wheat is similarly inherited than in bread wheat showing a continuous variation (Prat et al., ; Somers, Fedak, Clarke, & Cao, ) with a high impact of genotype × environment interaction (Miedaner & Longin, ). The range from high to low susceptibility, however, is smaller than in bread wheat (Prat et al., ). Thirteen quantitative trait loci (QTL) for FHB resistance on 11 chromosomes were reported (Prat, Buerstmayr, Steiner, Robert, & Buerstmayr, ).…”
Section: Introductionmentioning
confidence: 99%
“…These landraces are treasured sources that were often used in wheat improvement (Lopes et al 2015;Soriano et al 2016). Alike wild durum progenitor (chapter 3), landraces convey valuable resistance genes that were used to enhance durum wheat resistance to various fungal diseases (Prat et al 2017;Rahman et al 2017), which thus stirred our interest.…”
Section: Genetic Makeup Of Durum Wheat Resistance To Stb: the Drasticmentioning
confidence: 99%
“…The limited scientific efforts and the so-called 'genetic erosion' underlined by several studies Soleimani et al 2002) gave rise to a higher vulnerability of durum wheat germplasm to the majority of biotic constrains, in particular to fungal diseases such as Fusarium head blight and leaf rust (Prat et al 2017). …”
mentioning
confidence: 99%